2008
DOI: 10.3923/pjbs.2008.2048.2050
|View full text |Cite
|
Sign up to set email alerts
|

Response of Mungbean Varieties to Different Sowing Dates

Abstract: In order to investigate the effect of sowing dates on yield and yield components of mungbean varieties a two years field experiment was conducted during 2005 and 2006 in Iran. The experimental design was split plot on the basis of randomized complete block design with four replications. Main plots consisted of three sowing dates (May 30, June 14, 29) and sub plots were also allocated to six varieties (Partow, vc1973, vc1178, vc4152, NM92 and Pusa1973). Results of combined analysis showed that seed yield was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Sattya was recorded with significantly minimum pod length. Similar variation among mungbean genotypes in respect of yield attributes was also confirmed by Miah et al,2009, Sarkar et al (2004 and Sadeghipour (2008).…”
Section: Results and Discussion Phenologysupporting
confidence: 80%
See 1 more Smart Citation
“…Sattya was recorded with significantly minimum pod length. Similar variation among mungbean genotypes in respect of yield attributes was also confirmed by Miah et al,2009, Sarkar et al (2004 and Sadeghipour (2008).…”
Section: Results and Discussion Phenologysupporting
confidence: 80%
“…During 2016 biological yield obtained with 2 nd fortnight June and 1 st fortnight of July sown crop were significantly at par. Singh et al (2015), Ram et al (2016), Sarkar et al (2004) and Sadeghipour (2008) had also reported higher seed and biological yield in early sown mungbean due to higher temperature conditions under delayed conditions. The biological yield differed significantly among mungbean genotypes during both years of study.…”
Section: Results and Discussion Phenologymentioning
confidence: 94%
“…Low temperature at the sowing time (Feb 26) is also responsible for proper plant stand and uniform growth. Thus the crop sown after March 11 harboured by quite higher temperature than 35 0 C (Table 2) at reproductive phase of the crop which affected seed development and finally resulted lower seed yield and its quality parameters Dhanjal et al (2000), Ram et al (2000) and Sadeghipour, (2008) reported that sowing of mungbean in first fortnight of March temperature were in favour of germination and better growth resulted higher values of yield attributing characters and better diversion of photosynthates into grain yield. Higher grain yield of mungbean under March 11 sowing was probably due to higher grain yield per plant which was because of its attributes viz.…”
Section: Resultsmentioning
confidence: 99%
“…Good yield performance can be achieved by proper combination of agro technical measures (Sarkar et al 2004;Rajput et al, 1992;Nazir 1996;Boe et al, 1991;El Karamany, 2006;Mansoor, 2007;Sadeghipour, 2008). In this trial appropriate time of sowing, plant density and line to line spacing were applied to provide available sunlight and aeration as well as more space and nutrition in the root zone.…”
Section: Discussionmentioning
confidence: 99%